Peningkatan Kontras Menggunakan Metode Contrast Limited Adaptive Histogram Equalization Pada Citra Paru-Paru Yang Kecanduan Rokok - Fitri Handayani Lubis; Muhammad Syahrizal; Kennedi Tampubolon; Sinar Sinurat (JURIKOM (Jurnal Riset Komputer), 2021)
Image (Citra) is a combination of points, lines, fields, and colors to create an imitation of an object, usually a physical or human object. The use of digital images is increasing because of the advantages possessed by digital images, including the ease in getting images, reproducing images, processing images and others. The problem of contrast in the image captured by the camera is often some interference with the results of the captured image. For example, the image is accompanied by a lack of sharp increase in light, or weak in terms of contrast so that the object is very difficult to separate through operations containing because too much interference or contrast in the image. Based on the problem, to improve the image with less contrast it is necessary to increase the contrast by using the contrast limited adaptive method. contrast limited adaptive image is said to be good if it is able to involve all levels or levels. Of course the goal is to be able to display details in the image so that it is easily observed.